Physical Pain as Pleasure: A Theoretical Perspective. Issue 4 (3rd May 2020) - Dunkley, Cara R.; Henshaw, Craig D.; Henshaw, Saira K.; Brotto, Lori A.
Abstract : Physical pain represents a common feature of Bondage and Discipline/Dominance and Submission/Sadism and Machochism (BDSM) activity. This article explores the literature accounting for how painful stimuli may be experienced as pleasurable among practitioners of BDSM, and contrasting this with how it is experienced as painful among non-BDSM individuals. We reviewed the available literature on pain and on BDSM, and used the findings to postulate a theory accounting for how painful stimuli are experienced as pleasurable. Our theory was then checked with BDSM practitioners. The emotional, physiological, and psychological elements of pain interact to facilitate the experience of pain as pleasure in BDSM. A multitude of interconnected factors was theorized to alter the experience of BDSM pain, including: neural networks, neurotransmitters, endogenous opioids and endocannabinoids, visual stimuli, environmental context, emotional state, volition and control, interpersonal connection, sexual arousal, and memories. The experience of pain in this context can bring about altered states of consciousness that may be similar to what occurs during mindfulness meditation. Through understanding the mechanisms by which pain may be experienced as pleasure, the role of pain in BDSM is demystified and, it is hoped, destigmatized.